Fabrication of three-dimensional PCL/BiFeO3 scaffolds for biomedical applications - DUMLUDAĞ, FATİH; GÜNDÜZ, OĞUZHAN (ELSEVIER, 2020)
The aim of this study is to examine the pH effect on bismuth ferrite (BiFeO3) properties and observe the BiFeO3 behaviour in the polycaprolactone (PCL). In this paper, BiFeO3 was synthesized via co-precipitation method at three different pH values (10.64, 11.32, and 11.58). These produced particles were added into the 25wt %PCL solutions separately to get the scaffolds using a 3D printing process. Crystallite sizes were determined from the Debye-Scherer formula using XRD. With different pH values, crystal sizes were found as 15, 12, and 10 nm and particle sizes determined from SEM were 142, 134, and 111.39 nm for 10.64, 11.32, and 11.58, respectively. The adenocarcinoma lung cancer cell (A549) adhesion on the scaffolds revealed that cells could attach to the scaffolds. Maximum dielectric constant values were obtained for the pellets and scaffolds as 10.37 nF and 6.16 nF for the pellet BiFeO3 (pH = 11.58) and the scaffold 25wt. 0 /01 3 CL/2wt.%BiFeO3 (pH = 11.58), respectively.
Keywords: Bismuth ferrites; Co-precipitation method; Conductivity; Dielectric constant; Multiferroics; 3D printing process